Social marketing and social change : strategies and tools for health, well-being, and the environment - Lefebvre, R. Craig, 1959- (San Francisco, CA : Jossey-Bass, 2013)
"Focusing on the use of marketing principles and techniques to develop population-based health promotion and disease prevention programs, this book features a practical emphasis for incorporating a marketing orientation and marketing techniques to address the diverse range of issues and problems that are encountered in the practice of public health. Its comprehensive view of social marketing includes its research base, its applications to a diverse set of social problems, and the focus on the public health field. The book promotes social marketers as scientists-practitioners who must understand the theory and research of social marketing as it is applied to designing effective social change programs"--Provided by publisher.
Includes bibliographical references (p. [505]-540) and index.
Business Administration
Keywords: Marketing of Health Services -- methods; Health Promotion -- methods; Social Change; Social Marketing